INCREASING THE INVESTMENT ATTRACTIVENESS OF REGIONS TO ENSURE FINANCIAL STABILITY (E Conference Zone, 2024)
Sustained high interest rates in the global economy, conflicts between countries, low rates of international trade, and natural disasters caused by climate change have a significant impact on global economic growth. The global economic growth rate of the world economy is projected to reach 2.4 percent in 2023, which is lower than the 3 percent growth rate recorded before the pandemic in 2024.